1984
DOI: 10.1143/ptp.71.985
|View full text |Cite
|
Sign up to set email alerts
|

A Spectroscopic Study of the 21 Ne Hypernucleus

Abstract: 985A study of :',lNe hypernucleus is carried out within the framework of a+ 16 0+A cluster model dynamics. The positive and negative parity states are analyzed in detail by calculating energy spectra, r. m. s. radii, B(E2) values and reduced widths to the 2°Ne+A, a+~70 and ~He+160 channels. The obtained states constitute various kinds of rotational bands. Emphasis of discussion is put on the structure characteristics of these rotational bands and on the glue·like effects generated by a A particle coupled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(124 citation statements)
references
References 5 publications
5
119
0
Order By: Relevance
“…In all cases, s reduces quadrupole deformation. This is consistent with cluster model calculations [22,27] and (relativistic) mean-field calculations [3][4][5] that have demonstrated the reduction of β by s . On the other hand, it is found that p increases β.…”
Section: A General Trend Of the Energy Curvessupporting
confidence: 90%
See 3 more Smart Citations
“…In all cases, s reduces quadrupole deformation. This is consistent with cluster model calculations [22,27] and (relativistic) mean-field calculations [3][4][5] that have demonstrated the reduction of β by s . On the other hand, it is found that p increases β.…”
Section: A General Trend Of the Energy Curvessupporting
confidence: 90%
“…Our result shows the opposite trend to their result: Since the positive-parity state is more deformed than the negative-parity state, the binding of s is weaker when it is coupled to the negative-parity state. This trend is common to other calculations, including the cluster model calculation for 21 Ne [22]. However, AMD fails to reproduce the small excitation energy of the negative-parity state and does not have prominent α + 15 O clustering; both of these results are mainly due to the lack of angular momentum projection and the GCM calculation.…”
Section: B Discussion On Each Hypernucleussupporting
confidence: 57%
See 2 more Smart Citations
“…For example, the parity inversion of the 20 Λ Ne ground state was predicted [5]. In 21 Λ Ne, it was predicted that the Λ hyperon generates various α+ 16 O +Λ cluster states and mean-field-like states [6,7]. The difference between these structures leads to the difference in the Λ binding energies and the reduction of the B(E2) [7].…”
Section: Introductionmentioning
confidence: 99%